2023
DOI: 10.1371/journal.pone.0281066
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of birth injuries and associated factors among newborns delivered in public hospitals Addis Ababa, Ethiopia, 2021. Crossectional study

Abstract: Background Birth injury is harm that a baby suffers during the entire birth process. It includes both birth asphyxia and birth trauma. In Ethiopia, birth injury has become the leading cause of neonatal morbidity and mortality, accounting around 28%-31.6% of neonatal mortality. The study aimed to assess the prevalence and factors associated with birth injuries among newborns delivered in public hospitals Addis Ababa, Ethiopia, 2021. Methods Institution based cross-sectional study was conducted from February 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(30 citation statements)
references
References 22 publications
3
27
0
Order By: Relevance
“…Sensitivity analysis was done by removing outliers and inliers, and no significant difference was investigated. While removing outliers, we noticed that the pooled prevalence of neonatal birth trauma was 15% (95% CI [12][13][14][15][16][17][18], and after removing inliers, the pooled prevalence was 14% (95% CI 12-15), so we can say this metaanalysis result is not sensitive.…”
Section: Sensitivity Analysismentioning
confidence: 98%
See 2 more Smart Citations
“…Sensitivity analysis was done by removing outliers and inliers, and no significant difference was investigated. While removing outliers, we noticed that the pooled prevalence of neonatal birth trauma was 15% (95% CI [12][13][14][15][16][17][18], and after removing inliers, the pooled prevalence was 14% (95% CI 12-15), so we can say this metaanalysis result is not sensitive.…”
Section: Sensitivity Analysismentioning
confidence: 98%
“…Not applicable. 8,10,13,16 Random Less 24 (13-36) 83. 16 .00 Cephalohematoma [8][9][10]13,16 Random Marked 27 93.06 .00 Skeletal fractures 8,9,12,16 Random Marked 18 (4-32) 93.20 .00 Soft tissue injury 8,9,12,13,16 Random Marked 17 (5-48) 97.57 .00 Nerve injury 8,9,13,16 Random Less 13 (6-21) 74.24 .01…”
Section: Consent For Publicationmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of factors have been identified as predictors of birth injury in Africa. Maternal and fetal factors including macrosomia,14 15 17–19 place of birth,20 short height of the mothers,10 parity,9 12 educational status,9 place of residence,12 antenatal care,9 occupational status,9 sex of the neonate,10 14 birth weight,10 11 13 gestational diabetic mellitus10 and night-time birth 10. On the other hand, labour and delivery-related factors were duration of labour,10 11 15 fetal distress,10 12 instrumental delivery,10 11 13 14 17 cord prolapse,10 birth attended by residents,10 shoulder dystocia,11 fetal presentation and position 12–14…”
Section: Introductionmentioning
confidence: 99%
“…In LMICs, estimates from individual studies suggest that the cumulative incidence of birth-related trauma ranges from an estimated 3 per 1,000 live births [ 18 ] to 869 per 1,000 live births [ 19 ] in Africa; 3 per 1,000 live births [ 20 , 21 ] to 4.7 per 1,000 live births [ 22 ] in Asia and Pacific region; and 6.7 per 1,000 live births [ 23 ] to 87.3 per 1,000 live births [ 24 ] in the middle east. Operative vaginal deliveries such as vacuum extractions or forceps [ 25 34 ], fetal presentation other than vertex [ 25 , 26 , 30 , 31 , 35 , 36 ], shoulder dystocia [ 28 , 29 , 31 ], gestational age [ 35 ], prolonged labor [ 27 , 29 , 31 , 36 ], general anesthesia [ 35 ], and newborn birth weight greater than 4000 grams [ 26 , 29 , 30 , 34 , 36 ] have been found to increase the odds of sustaining birth trauma. Moreover, logistic regression analysis demonstrated that nulliparous women [ 25 , 28 ], lack of or inadequate antenatal care follow-up [ 29 , 30 , 32 , 36 ], gestational diabetes mellitus [ 36 ], residence in rural settings [ 25 , 26 , 30 ], maternal age [ 32 , 35 ], and abnormal fetal heart rate patterns [ 25 ] have been correlated with a statistically significant increase in neonatal birth trauma.…”
Section: Introductionmentioning
confidence: 99%